Velocity estimation of micro-particles driven by cavitation bubble collapses through controlled erosion experiments - Tan, Kheng Leong (2022)
The high-energy phenomenon of particle acceleration driven by cavitation bubble collapses has garnered research interests over the past few decades. Potential applications range from cavitation-induced drug delivery, chemical synthesis, sonochemistry to micro-machining operations. However, the acceleration mechanisms and the velocities attained by particles remain in huge contention. A novel particle velocity estimation model based on experimental mass loss input is put forward in this paper. Micro-abrasive particles, of 5 µm to 50 µm average diameter, were exposed to intense ultrasonic irradiation of 20 kHz in a deionized water medium for 10 min. The accelerated particles were captured by target specimens placed at 0.5 mm from the ultrasonic horn surface in a controlled experiment. Through the quantification of specimen mass loss, the average particle impact velocity could be estimated by a reverse solid particle erosion model. Results show that the magnitude of particle velocity is in the range of 8–40 m/s and is dependent on both particle size and ultrasonic amplitude. The results also suggest that micro-jet is the likely particle acceleration mechanism in the presence of a solid wall boundary from a microscopic perspective.